Preliminary results of geological characterization and geochemical monitoring of Sulcis Basin (Sardinia), as a potential CCS site. (September 2017) - Chiara Tartarello, Maria; Plaisant, Alberto; Bigi, Sabina; Eugene Beaubien, Stanley; Graziani, Stefano; Lombardi, Salvatore; Ruggiero, Livio; De Angelis, Davide; Sacco, Pietro; Maggio, Enrico
Abstract: The Sulcis Basin is an area situated in SW Sardinia (Italy) and is a potential site for the development of CCS in Italy. This paper illustrates the preliminary results of geological characterization of fractured carbonate reservoir (Miliolitico Fm.) and the sealing sequence, composed by clay, marl and volcanic rocks, with a total thickness of more than 900 m. To characterize the reservoir-caprock system an extensive structural-geological survey at the outcrop was conducted. It was also performed a study of the geochemical monitoring, to define the baseline conditions, measuring CO2 concentrations and flux in the study site.